2023
DOI: 10.3389/fphar.2023.1153070
|View full text |Cite
|
Sign up to set email alerts
|

Overview of systematic reviews of probiotics in the prevention and treatment of antibiotic-associated diarrhea in children

Abstract: Background: Antibiotics alter the microbial balance commonly resulting in antibiotic-associated diarrhea (AAD). Probiotics may prevent and treat AAD by providing the gut barrier and restoring the gut microflora. This study will overview the Systematic Reviews (SRs) of probiotics in preventing and treating AAD in children. It will also assess the reporting, methodological, and evidence quality of the included SRs to provide evidence for their clinical practice.Methods: After searching PubMed, Embase, Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The incidence of antibiotic-related diarrhea remains relatively high especially in hospitalized children and older adults ( Kaya et al, 2023 ; Zhao et al, 2023 ). The effectiveness of probiotic strains in the prevention and treatment of antibiotic-associated diarrhea has been well-summarized in recent systematic literature reviews ( Doar and Samuthiram, 2023 ; Yang et al, 2023 ). However, few studies could be found concerning probiotic regulation on antibiotic-associated diarrhea by targeting AQPs.…”
Section: Role and Regulation Of Aqp3 Expression In Diarrheamentioning
confidence: 99%
“…The incidence of antibiotic-related diarrhea remains relatively high especially in hospitalized children and older adults ( Kaya et al, 2023 ; Zhao et al, 2023 ). The effectiveness of probiotic strains in the prevention and treatment of antibiotic-associated diarrhea has been well-summarized in recent systematic literature reviews ( Doar and Samuthiram, 2023 ; Yang et al, 2023 ). However, few studies could be found concerning probiotic regulation on antibiotic-associated diarrhea by targeting AQPs.…”
Section: Role and Regulation Of Aqp3 Expression In Diarrheamentioning
confidence: 99%